Skipping Christmas - Grisham, John. (New York : Doubleday, 2001)
Luther and Nora Krank decide to avoid the chaos and frenzy of Christmas by taking a Caribbean cruise during the holidays, but their plans have unexpected consequences.
Accelerated Reader AR
Keywords: Christmas stories